USWAH HASANAH MANAGEMENT BASED ON STUDENT CHARACTER BUILDING IN MODERN ISLAMIC INSTITUTION - Moh Ikrom Mubarok; Sukarno Sukarno; Minnah El-Widdah (JURNAL AL-TANZIM, 2021)
Lately, parents are faced with problems that should not be ignored, namely moral and moral issues, which will become a severe problem in the future. This article is here to explain clearly the implementation of uswah hasanah education in character building in Islamic boarding schools as exemplified by Rasulullah SAW in everyday life, especially in the dormitory of the new students of Pondok Modern Darussalam Gontor campus 10 Jambi. In this study, the authors used a qualitative approach with case study. From the research that has been carried out, it is found that the role of the dormitory supervisor teacher and dormitory administrator in terms of good, especially the habit of living disciplined in all things and inculcating the spirit of ukhuwah Islamiyah is a vital instrument in the formation of the Islamic character of new students.